2007
DOI: 10.1186/1471-2148-7-196
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific evolution of immune receptor tyrosine based activation motif-containing CEACAM1-related immune receptors in the dog

Abstract: Background: Although the impact of pathogens on the evolution of the mammalian immune system is still under debate, proteins, which both regulate immune responses and serve as cellular receptors for pathogens should be at the forefront of pathogen-driven host evolution. The CEA (carcinoembryonic antigen) gene family codes for such proteins and indeed shows tremendous species-specific variation between human and rodents. Since little is known about the CEA gene family in other lineages of placental mammals, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 48 publications
1
42
1
Order By: Relevance
“…It is generally accepted that PSGs evolved exclusively in mammals with hemochorial placentation. In cattle (epitheliochorial placenta) and dogs (endotheliochorial placenta), PSGs did not evolve (Kammerer et al 2004, Kammerer et al 2007.…”
Section: Introductionmentioning
confidence: 95%
“…It is generally accepted that PSGs evolved exclusively in mammals with hemochorial placentation. In cattle (epitheliochorial placenta) and dogs (endotheliochorial placenta), PSGs did not evolve (Kammerer et al 2004, Kammerer et al 2007.…”
Section: Introductionmentioning
confidence: 95%
“…All 12 expressed CEACAM genes and a number of derived pseudogenes cluster on chromosome 19q13 [3,4]. CEACAMs show distinct expression patterns on different cell types [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…They have been extensively used to study the polarized organization of epithelial cells forming monolayers and the biosynthetic and recycling pathways for apical and basolateral plasma‐membrane proteins (Rodriguez‐Boulan et al ., 2005). It has been reported that most of the CEACAMs, identified in canine liver, bone marrow, spleen, peripheral blood monocytes and granulocytes, harboured immunoreceptor tyrosine‐based activation motifs, one of which, CEACAM28, exhibits nearly complete sequence identity with the ligand‐binding N domain of CEACAM1 (Kammerer et al ., 2007). In consequence, MDCK cells probably express canine CEACAMs.…”
Section: Introductionmentioning
confidence: 99%